Need for nurses’ education on pressure ulcer prevention in bedridden patients at the General Reference Hospital, Kinshasa, DRC - Jean-Paul DIWOTO DOWO; Nsopa Emilie Kulembidila; Tshimbila Franck Kabambi; Lumonansoni Benjamin Lumbanziladio; Mademvo Oscar Ngoma; Ntela Simon-Decap Mabakutuvangilanga; Jiwe Jean-Pierre Amuli (Orapuh Journal)
Introduction